(untitled) (Research, Society and Development, 2022)
Objective: Identify the facilitating and hindering factors for communication with health professionals, from the perspective of hospitalized patients, in the Medical Clinic, and to describe these patients’ expectations regarding the communication between them and the health professionals, during hospitalization. Methods: descriptive study with a qualitative approach. The research involved 13 patients hospitalized in the Internal Medicine sector of a Teaching Hospital in Minas Gerais. Data collection took place through semi-structured audio interviews recorded between December/2019 and January/2020. Data analysis followed the Content Analysis, thematic modality. Results: three thematic categories emerged: Unpreparedness of the health professional, lack of dialogue and fragile reception; A horizontal and dialogical relationship between health professionals and patients favors communication and the patient’s perspectives in relation to communication with health professionals during hospitalization. The thematic categories revealed the perceptions of patients, hospitalized in the Medical Clinic, regarding the facilitating aspects and difficulties of their communication with health professionals, as well as their expectations regarding this communicational process. Final Considerations: respect, dialogue, acceptance and attention are fundamental to the basis of an effective communication. However, the lack of them constitutes a barrier, impacting the relationship of trust between health professionals and patients.